The First US Clinical Experience With Computer-Assisted Propofol Sedation: A Retrospective Observational Comparative Study on Efficacy, Safety, Efficiency, and Endoscopist and Patient Satisfaction. (September 2017) - Lin, Otto S.; Kozarek, Richard A.; Tombs, Deborah; La Selva, Danielle; Weigel, Wade; Beecher, Ryan; Jensen, Ana; Gluck, Michael; Ross, Andrew
Abstract : BACKGROUND: Computer-assisted propofol sedation (CAPS) is now approved for moderate sedation of American Society of Anesthesiologists (ASA) class I and II patients undergoing routine endoscopy. As the first US medical center to adopt CAPS for routine clinical use, we compared patient and endoscopist satisfaction with CAPS versus midazolam and fentanyl (MF) sedation. METHODS: Patients who underwent elective outpatient upper endoscopy and colonoscopy with CAPS were compared with concurrent patients sedated with MF. The primary end points were patient satisfaction (measured by the validated Patient Sedation Satisfaction Index [PSSI]), and endoscopist satisfaction (Clinician Sedation Satisfaction Index [CSSI]). Secondary end points included procedural success rates, polyp detection rates, adverse events, and procedure/recovery times. Multivariable regression was used for comparative analysis. RESULTS: CAPS was utilized to sedate 244 patients, of whom 55 underwent upper endoscopy, 173 colonoscopy, and 16 double procedures. During the same period, 75 upper endoscopies, 223 colonoscopies, and 30 doubles were performed with MF on similar patients. For upper endoscopy, the procedural success rate was 98.2% for CAPS versus 98.7% for MF ( P = .96), whereas for colonoscopy, the success rate was 98.9% vs 98.8% ( P = .59). Colonoscopic polyp detection rate was 54.5% for CAPS and 59.3% for MF ( P = .67). Procedure times were similar between CAPS and MF. For CAPS, the mean recovery time was 26.4 vs 39.1 minutes for MF ( P < .001). One CAPS patient required mask ventilation, 4 experienced asymptomatic hypotension or desaturation, and 5 experienced marked agitation resulting from undersedation. For MF, 5 patients had hypotension or desaturation, and 8 experienced undersedation. For colonoscopy, the CAPS group had higher PSSI scores for sedation adequacy, the recovery process and global satisfaction, and higher CSSI scores for ease of sedation administration, the recovery process and global satisfaction. For upper endoscopy and doubles, the CAPS CSSI score was higher for the recovery process only. All P values were adjusted for confounding by using regression analysis. CONCLUSIONS: In low-risk patients, CAPS appears to be effective and efficient. CAPS is associated with higher satisfaction than MF for colonoscopies and, to a lesser extent, upper endoscopies. Abstract : Supplemental Digital Content is available in the text.Published ahead of print March 17, 2017.